2023
DOI: 10.1108/rpj-02-2023-0068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scan speed on corrosion and tribocorrosion properties of cobalt-chromium alloy in situ produced by selective laser melting

Raghad Ahmed Alaloosi,
Onur Çomakli,
Mustafa Yazici
et al.

Abstract: Purpose This paper aims to investigate the influence of scan speed on the corrosion and tribocorrosion features of the CoCrMoW samples fabricated via the selective laser melting (SLM) process. Design/methodology/approach CoCrMoW samples were produced by SLM at different scan speeds. Produced samples were made via structural surveys (X-ray diffraction examinations and scanning electron microscopic analyses), hardness measurements and electrochemical and tribocorrosion experiments. Findings Outcomes displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…23 The corrosion evaluations of latticetype (controlled porosity) CoCrMo (0.35 wt % C) specimens for bone ingrowth fabricated with LPBF showed a relatively high corrosion resistance in simulated body fluid. 24 In a recent study, 25 the influence of scan speed on the corrosion and tribocorrosion properties of LPBF CoCrMoW samples was examined, showing that the laser scan speed could directly affect the microstructure and subsequently impact the corrosion and tribocorrosion behavior of the samples. The surface of as-printed LPBF CoCrMo is very different from abraded/polished surfaces of either LPBF or traditionally manufactured CoCrMo and has been shown to influence corrosion and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The corrosion evaluations of latticetype (controlled porosity) CoCrMo (0.35 wt % C) specimens for bone ingrowth fabricated with LPBF showed a relatively high corrosion resistance in simulated body fluid. 24 In a recent study, 25 the influence of scan speed on the corrosion and tribocorrosion properties of LPBF CoCrMoW samples was examined, showing that the laser scan speed could directly affect the microstructure and subsequently impact the corrosion and tribocorrosion behavior of the samples. The surface of as-printed LPBF CoCrMo is very different from abraded/polished surfaces of either LPBF or traditionally manufactured CoCrMo and has been shown to influence corrosion and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion evaluations of lattice-type (controlled porosity) CoCrMo (0.35 wt % C) specimens for bone ingrowth fabricated with LPBF showed a relatively high corrosion resistance in simulated body fluid . In a recent study, the influence of scan speed on the corrosion and tribocorrosion properties of LPBF CoCrMoW samples was examined, showing that the laser scan speed could directly affect the microstructure and subsequently impact the corrosion and tribocorrosion behavior of the samples. The surface of as-printed LPBF CoCrMo is very different from abraded/polished surfaces of either LPBF or traditionally manufactured CoCrMo and has been shown to influence corrosion and biocompatibility. , LPBF CoCrMo fabricated in different building orientations (perpendicular and parallel to building direction) may or may not exhibit different corrosion behaviors, depending on the carbon content, heat treatment, and environmental conditions. , Our previous study suggested that a suitable biomedical manufacturing protocol, including low-carbon CoCrMo feed powder and a suitable heat treatment protocol, can eliminate any differences in building orientations …”
Section: Introductionmentioning
confidence: 99%